2009
DOI: 10.1111/j.1863-2378.2009.01246.x
|View full text |Cite
|
Sign up to set email alerts
|

Chicken Faeces Garden Fertilizer: Possible Source of Human Avian Influenza H5N1 Infection

Abstract: Avian influenza H5N1 infection in humans is typically associated with close contact with infected poultry or other infected avian species. We report on human cases of H5N1 infection in Indonesia where exposure to H5N1-infected animals could not be established, but where the investigation found chicken faeces contaminated with viable H5N1 virus in the garden fertilizer. Human cases of avian influenza H5N1 warrant extensive investigations to determine likely sources of illness and to minimize risk to others. Aut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 5 publications
2
17
0
1
Order By: Relevance
“…exposure to H5N1 contaminated environments may also lead to H5N1 infection [36], [49], [50], [51], [52]. Exposure to H5N1 virus in contaminated feces in garden fertilizer has been reported as a source of human infection [53]. Because birds are known to shed high concentrations of virus into water sources, transmission from poultry to humans through contaminated water is also possible [52].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…exposure to H5N1 contaminated environments may also lead to H5N1 infection [36], [49], [50], [51], [52]. Exposure to H5N1 virus in contaminated feces in garden fertilizer has been reported as a source of human infection [53]. Because birds are known to shed high concentrations of virus into water sources, transmission from poultry to humans through contaminated water is also possible [52].…”
Section: Resultsmentioning
confidence: 99%
“…Little is understood about non-direct contact exposures to H5N1-infected poultry that may increase the risk of human infection, though recent studies have suggested an association between exposure to a contaminated environment (e.g., water; cleaning poultry cages or their designated areas; using poultry feces for fertilizer) and infection either through ingestion, conjunctival or intranasal inoculation of contaminated water, soil [49], [51], [53] or via fomites e.g. equipment or vehicles [50].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In villages located far from the river, the alternative water source and water storage can be a small pond for washing/bathing, drinking/cooking, gardening and sometimes raising fish or ducks. Ducks that can potentially be infected by A(H5N1) virus have access to these communal ponds and may defecate/shed large quantities of virus in pond water [2022]. A(H5N1) infections in two children in Vietnam may be linked to swimming/bathing in canal water also accessed by ducks [23].…”
Section: Discussionmentioning
confidence: 99%
“…From the infected birds, the viruses get excreted through their respiratory tract, conjunctiva and faeces and spread through direct contact as well as indirectly by means of aerosols, virus contaminated soil, feed, water, faeces, equipments, fomites, etc. (Alexander 2001;FAO 2004;de Jong et al 2005;WHO 2006;Vong et al 2008Vong et al , 2009Kandun et al 2009). Another possible means of transmission is from the blood or body fluids of infected birds via slaughterhouse and other food processing practices (Greiner et al 2007), consumption of uncooked poultry products, improper waste disposal practices, etc.…”
Section: Avian Influenza (Bird Flu)mentioning
confidence: 97%